Abnormal psychology : neuroscience perspectives on human behavior and experience - Ray, William J., 1945- (Los Angeles : SAGE, 2015)
The purpose of this text is to bring together current perspectives concerning the manner in which the human mind, behavior, and experience can be understood. In addition to the traditional psychological literature, this book draws from work in the cognitive and affective neurosciences, epidemiology, ethology, and genetics. Its focus is on a unification and integration of these understandings within a broader consideration of human culture and language as it applies to abnormal psychology.
Includes bibliographical references and index.
Keywords: Psychology, Pathological; Mental Disorders